Prognostic role of salivary CD44sol levels in the follow‐up of laryngeal carcinomas. (7th November 2013) - Allegra, Eugenia; Trapasso, Serena; La, Alessandro; Aragona, Teodoro; Pisani, Davide; Belfiore, Antonino; Garozzo, Aldo
<x xml:space="preserve">Abstract</x> Background The purpose of this study was to verify CD44sol levels in the saliva of patients during follow‐up after surgery for laryngeal cancer, to compare them with those registered at the time of diagnosis (pre‐intervention) in the same patients, and to assess the reliability of the test as a prognostic indicator. Methods This prospective study was performed on 21 patients having laryngeal cancer who underwent surgery at the Division of Otolaryngology, University of Catanzaro; twelve adults with head and neck benign disease were recruited to form a control group. For each patient, the clinical–anamnestic data were collected and entered into a database. The sampling of undiluted saliva was performed the day before surgery and during the follow‐up, every 3 months. Salivary CD44sol levels were determined using the ELISA method. Results Mean salivary CD44sol levels in the patients group before surgery (pre‐intervention) were significantly higher than those in the control group (70.75 ± 33.8 vs. 12.4 ± 8.7 ng/ml). At follow‐up performed 3 months after surgery, 18 of 21 (85.71%) patients had a reduction in salivary CD44sol levels, with a mean value of 50.1 ng/ml; the difference between these and pre‐intervention CD44sol levels was statistically significant (P < 0.04). Mean CD44sol levels of 31.1 ng/ml at 6 months post‐intervention have been determined in 19 of 21 enrolled patients; none of the 19 patients have actual signs of recurrence. Conclusions These data seem to show that the determination of salivary CD44sol levels can represent a promising prognostic test in laryngeal carcinomas.